The Fund's Transparency Policy : Proposed Amendments. (Policy Papers; Policy Paper ;, 2005)
Provides a commentary on the main policy changes agreed by Executive Directors, provides a commentary on other amendments, many of which are designed to implement policy changes already agreed by the Executive Board in other contexts or to clarify the implementation of existing policies. Explains the original staff proposals that are not being retained. Reviews changes and clarifications endorsed by the Board that do not require an amendment to the transparency policy decision.